Associação da presença de Helicobacter pylori e dos genótipos caga e vaca com as alterações moleculares dos supressores tumorais P53 e P27 nos adenocarcinomas gástricos - André, Ângela Rosa (2008)
Gastric carcinoma is the second cause of death by cancer in the world. On State of Ceara-Brazil is the second most frequent type of cancer in men and third in women. Adenocarcinomas account for approximately 95% of all malignant gastric neoplasms. It has been associated to genetic and environmental factors and a intimate relationship between the infection by the bacteria Helicobacter pylori and the gastric carcinoma have been related. The presence of the cagA gene and specific genotypes (s1m1) of the gene vacA have been detected in more pathogenic strains. Although the precise molecular mechanisms by which H. pylori could promote the process of gastric carcinogenesis are under investigation, one hypothesized mechanism involves the tumor supressor genes inactivation. The aim of the present study was to verify if the presence of Helicobacter pylori, cagA and vacA genes is related to mutations in the tumor supressor gene p53 and altered expression of p53 and p27 proteins in gastric adenocarcinomas. Seventy-four (74) samples were analyzed to detect the presence of H. pylori, cagA and genotypes of vacA by Polymerization Chain Reaction (PCR). The mutational analysis of p53 gene was performed by PCR-SSCP (Polymerization Chain Reaction for analysis of the Single-strand Conformation Polymorphism). Analysis of mutation or overexpression of p53 protein and p27 expression was detected by the immunohistochemical method. The bacteria was detected in 95% of the samples, 63% was cagA(+). Among the vacA allele it was observed prevalence of s1 (74%) and m1 (82%), associated in 69% of the cases. Mutation analysis of p53 demonstrated 72% of the cases with altered electrophoretic mobility; The alterations were significatively more frequent in the presence of the cagA gene. Immunohistochemical analysis detected only 29% of cases with the expression of p53 protein. The protein p27 showed accentuated reduction in its expression (detected in only 19% of the cases), it has not demonstrated compensatory activity in relation to the p53 altered protein, neither association to H. pylori presence. Finally, these data suggest that simultaneous inactivation of these tumor suppressors genes may be the key point of deregulation of the cellular cycle that, associated to the other factors, favor the development and progression of the gastric cancer. There is some evidence that the bacterial presence, cagA and vacA/s1m1 genes, may influence, in a not understood way, the alterations observed in the tumor suppressors p53 and p27.